Permasalahan Normatif Pengelolaan Sampah Perkotaan di TPST Bantar Gebang dalam Menjamin Hak atas Lingkungan Hidup yang Baik dan Sehat - Zorya Kanoubie Attar Bakhri (Advances In Education Journal, 2025)
Urban waste management constitutes an environmental issue that extends beyond technical sanitation concerns and is closely linked to the state’s legal obligation to guarantee the right to a good and healthy environment. This article examines the normative problems of urban waste management at the Bantar Gebang Integrated Waste Management Site (TPST) within the framework of environmental law and human rights. The research employs a normative juridical method, using statutory and conceptual approaches. The data are secondary in nature and were collected through library research, including legislation, legal doctrines, and relevant academic literature. The findings indicate that, at the normative level, the Indonesian legal system has established a relatively comprehensive regulatory framework governing waste management and environmental protection, as reflected in the 1945 Constitution, Law Number 18 of 2008 on Waste Management, and Law Number 32 of 2009 on Environmental Protection and Management. However, in practice, waste management at TPST Bantar Gebang reveals a significant gap between legal norms and policy implementation. Indications of environmental pollution, unequal distribution of environmental burdens, and the weak application of environmental law principles demonstrate that the state’s obligation to ensure the right to a good and healthy environment has not been fully realized in a substantive manner.